Medical Work on Leprosy at Morgenster Mission and Ngomahuru, colonial Zimbabwe (Southern Rhodesia),1899-1945 - Masango, Natsai Nicole (Stellenbosch : Stellenbosch University, 2026)
Thesis (MA)--Stellenbosch University, 2026.